2006
DOI: 10.1007/s00213-006-0545-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of paroxetine on enhanced contextual fear induced by single prolonged stress in rats

Abstract: Our results suggest that SPS can reproduce behavioral alteration similar to that observed in patients with PTSD, and this elevated fear response can be alleviated by the chronic administration of PRX at doses producing clinically relevant serum concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
87
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(98 citation statements)
references
References 43 publications
(45 reference statements)
8
87
2
1
Order By: Relevance
“…Apparently, this finding is contradictory to the lack of effect on memory reconsolidation of stressed rats after MDZ administration observed in the current research. It is noteworthy that stress experience strengthened fear memory and this influence is revealed by two main effects: (a) enhanced fear retention or fear expression as previously demonstrated using the SPS (Takahashi et al, 2007;Kohda et al, 2007) and/or (b) the impairment of fear extinction or the resistance to extinguish (Rodr铆guez Manzanares et al, 2005;Akirav and Maroun, 2007;Yamamoto et al, 2008). In contrast, Zhang and Cranney (2008) found no increase of fear expression and no alteration of extinction rate in the rats subjected to modified SPS, despite increased anxiety as evidenced in an elevated plus-maze test.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Apparently, this finding is contradictory to the lack of effect on memory reconsolidation of stressed rats after MDZ administration observed in the current research. It is noteworthy that stress experience strengthened fear memory and this influence is revealed by two main effects: (a) enhanced fear retention or fear expression as previously demonstrated using the SPS (Takahashi et al, 2007;Kohda et al, 2007) and/or (b) the impairment of fear extinction or the resistance to extinguish (Rodr铆guez Manzanares et al, 2005;Akirav and Maroun, 2007;Yamamoto et al, 2008). In contrast, Zhang and Cranney (2008) found no increase of fear expression and no alteration of extinction rate in the rats subjected to modified SPS, despite increased anxiety as evidenced in an elevated plus-maze test.…”
Section: Discussionsupporting
confidence: 66%
“…What is more, under the present experimental protocol, baseline levels of fear averaged 70-80% during reactivation in unstressed rats. Other authors have shown that the exposure to a single-prolonged stress (SPS) protocol resulted in a facilitated contextual fear memory 1 week, but not 1 day after such stressful stimuli (Takahashi et al, 2007;Kohda et al, 2007). Zhang and Cranney (2008) described, using a modified SPS, that MDZ interfered fear memory reconsolidation even in stressed rats.…”
Section: Discussionmentioning
confidence: 99%
“…SPS rats underwent the SPS procedure on the first day. The SPS protocol was based on a combined plural stress paradigm (7,20): immobilization (compression with plastic bags) for 2 h, forced swimming for 20 min (24卤1藲C), rest for 15 min, followed by drying and ether anesthesia (until consciousness was lost).…”
Section: Methodsmentioning
confidence: 99%
“…These neuroendocrine findings specific to PTSD have served as the basis for animal models that are useful for elucidating the pathophysiology of PTSD. Singleprolonged stress (SPS) is a reliable animal model of PTSD based on the time-dependent dysregulation of the HPA axis and has been developed and employed for PTSD research (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the present study, a rat model of PTSD was built following the previously established SPS protocol (17,18), and immunohistochemistry, reverse transcription-polymerase chain reaction (RT-PCR) and western blotting analysis approaches were used to identify the expression of VDR in the rat hippocampal cells. In addition, the expression of LVSCC-A1C protein and mRNA was examined, as well as the Ca 2+ levels.…”
Section: Introductionmentioning
confidence: 99%